The design student's journey understanding how designers think - Lawson, Bryan (Routledge, 2019)
"Being a professional designer is one of the most intellectually rewarding careers. Learning to become a designer can be tremendous fun but it can also be frustrating and at times painful. What you have to do to become a designer is not often clearly laid out and can seem mysterious. Over the past 50 years or so we have discovered a great deal about how designers think. This book relies upon that knowledge but presents it in a way specifically intended to help the student and perhaps the teacher. Bryan Lawson’s classic book How Designers Think has been in print since 1980 and has gone through four editions to keep it up to date. This book can be seen as a companion volume for the design student."--